2021
DOI: 10.1016/j.celrep.2021.108807
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of gut microbiome reveals the role of bacterial folate and homocysteine metabolism in Parkinson’s disease

Abstract: Highlights d Microbiome functional analysis reveals changes in carbohydrate-active enzymes in PD d Higher number of bacterial mucin and host degradation enzymes link to PD d Metabolic modeling reveals the contribution of bacterialspecific metabolism in PD d Gut-community modeling reveals the role of bacterial folate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 71 publications
5
82
0
Order By: Relevance
“…Decreased long-chain acylcarnitines due to insufficient β-oxidation has been shown to carry potential for early diagnosis of Parkinson’s 28 , especially 12–14 long chain acylcarnitines. In recent work studying the gut microbiome, Rosario et al 29 have shown the role of bacterial folate and homocysteine metabolism in PD. Higher numbers of bacterial mucin and host degradation enzymes were linked to the manifestation of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased long-chain acylcarnitines due to insufficient β-oxidation has been shown to carry potential for early diagnosis of Parkinson’s 28 , especially 12–14 long chain acylcarnitines. In recent work studying the gut microbiome, Rosario et al 29 have shown the role of bacterial folate and homocysteine metabolism in PD. Higher numbers of bacterial mucin and host degradation enzymes were linked to the manifestation of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent work studying the gut microbiome, Rosario et al . (2021) 22 have shown the role of bacterial folate and homocysteine metabolism in PD. Higher numbers of bacterial mucin and host degradation enzymes were linked to the manifestation of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased long-chain acylcarnitines due to insufficient β-oxidation has been shown to carry potential for early diagnosis of Parkinson's 21 , especially 12-14 long chain acylcarnitines. In recent work studying the gut microbiome, Rosario et al (2021) 22 have shown the role of bacterial folate and homocysteine metabolism in PD. Higher numbers of bacterial mucin and host degradation enzymes were linked to the manifestation of PD.…”
Section: Serum Metabolomementioning
confidence: 99%
“…Although still controversial, several lines of evidence from metagenomic studies of PD patients and healthy age-matched individuals suggest dysbiosis within the gut microbiome of PD patients could modify the risk and progressively worsen disease status (Sampson et al, 2016;Qian et al, 2020;Romano et al, 2021). Despite methodological differences across studies, including inclusion criterion, sample collection, disease status, or additional confounders, contributing to divergent microbial profiles, the evidence of microbial dysbiosis in PD is consistent (Romano et al, 2021;Rosario et al, 2021). Individuals with PD have dramatically divergent microbial profiles compared to healthy controls (Romano et al, 2021).…”
Section: Gut Microbiome and Neurodegenerative Diseases Parkinson's Di...mentioning
confidence: 99%
“…As dietary fiber is vital for maintaining the colonic mucus barrier, fiber deficiency favors the proliferation of distinct microbial populations that degrade the colonic mucus layer and enable enhanced colonization and infiltration of opportunistic pathogens (Desai et al, 2016). Akkermansia spp., relatively sparse in healthy subjects, are consistently enriched in PD samples versus controls (Hill-Burns et al, 2017;Wallen et al, 2020;Rosario et al, 2021) and are increasingly abundant in the fecal microbiome of patients who experience constipation, a primary non-motor symptom of PD. Nishiwaki et al (2020) implicated this genus in the neuropathological progression of PD by mechanisms of degrading mucin.…”
Section: Gut Microbiome and Neurodegenerative Diseases Parkinson's Di...mentioning
confidence: 99%